Conventional Banking Super Apps: Perspectives from Generation Z: Aplikasi Super Perbankan Konvensional: Perspektif Generasi Z - Windyaningsih, Mia; Fauzi, Rizal Ahmad; Ermawati, Wita Juwita (Universitas Muhammadiyah Sidoarjo, 2025)
Super Apps are versatile applications that integrate various financial services within a single platform. The Super Apps referred to in this research belong to conventional banks, such as Wondr by BNI, Bale by BTN, Livin' by Mandiri, BRImo by BRI, myBCA, and BYOND by BSI. Amidst an increasingly competitive financial landscape with the presence of digital banks and fintech, understanding Generation Z's preferences becomes crucial, given that they are the largest digital users and the banking industry's primary future market. This research endeavors to identify and analyze the factors influencing Generation Z's interest in using conventional bank Super Apps. The framework implemented is a quantitative associative approach; data was procured from 110 Generation Z respondents through purposive sampling. Multiple regression analysis was applied to the variables of convenience (X1), environmental influence (X2), service features (X3), digital experience (X4), bank reputation (X5), and promotion (X6) on the interest in using Super Apps (Y). The results show that convenience, environmental influence, digital experience, and bank reputation significantly affect interest. However, service features and promotion were not found to have a significant influence. These findings provide crucial insights for conventional banks in developing effective strategies to attract Generation Z.